Inactivation of UDP-Glucose Sterol Glucosyltransferases Enhances Arabidopsis Resistance to Botrytis cinerea - Castillo, Nidia; Pastor, Victoria; Chávez, Ángel; Arró, Montserrat; Boronat, Albert; Flors, Victor; Ferrer, Albert; Altabella, Teresa (Frontiers in Plant Science, 2019)
Free and glycosylated sterols are both structural components of the plasma membrane that regulate their biophysical properties and consequently different plasma membrane-associated processes like plant adaptation to stress or signalling. Several reports relate changes in glycosylated sterols levels with the plant response to abiotic stress, but the information about the role of these compounds in the response to biotic stress is scarce. In this work, we have studied the response to the necrotrophic fungus Botrytis cinerea in an Arabidopsis mutant that is severely impaired in steryl glycosides biosynthesis due to the inactivation of the two sterol glucosyltransferases (UGT80A2 and UGT80B1) reported in this plant. This mutant exhibits enhanced resistance against B. cinerea when compared to wild-type plants, which correlates with increased levels of jasmonic acid (JA) and up-regulation of two marker genes (PDF1.2 and PR4) of the ERF-branch of the JA-signalling pathway. Upon B. cinerea infection the ugt80A2;B1 double mutant also accumulates higher levels of camalexin, the major Arabidopsis phytoalexin, than wild-type plants. Camalexin accumulation correlates with enhanced transcript levels of several cytochrome P450 camalexin biosynthetic genes, as well as of their transcriptional regulators WRKY33, ANAC042 and MYB51, suggesting that the Botrytis-induced accumulation of camalexin is coordinately regulated at the transcriptional level. After fungus infection the expression of genes involved in the indole glucosinolate biosynthesis is also up-regulated at higher degree in the ugt80A2;B1 mutant than in wild type plants. Altogether the results of this study show that glycosylated sterols play an important role in the regulation of Arabidopsis response to B. cinerea infection, and suggest that this occurs through signaling pathways involving the canonical stress-hormone JA and the tryptophan-derived secondary metabolites camalexin and possibly also indole glucosinolates.